Effect of Prewetting Cenospheres on Hydration Kinetics, Microstructure, and Mechanical Properties of Refractory Castables - Ina Pundienė; Jolanta Pranckevičienė (Crystals)
This study investigated the effect of non-prewetted and prewetted cenospheres (CSs) on the hydration course and physical and mechanical properties of refractory castable mixtures incorporated with nano silica (NS). The fixed amount of 0.1% of NS improves the compressive strength of the refractory castable, containing various proportions of non-prewetted and prewetted CSs (up to 25% in composition). It was found that an increase in CSs slows down the hydration of cement and the early structure formation of refractory castable mixtures. Proportionally, due to the increase in the amount of non-prewetted and prewetted CSs in the composition, the density of the samples decreases from 1875 kg/m3 to 1310 kg/m3 after firing. The amount of CSs varied from 15 to 25% in the composition, increasing compressive strength by up to 5.3% and 8.6% in the case of non-prewetted CSs and by up to 39.2% and 20.5% in the case of prewetted CSs after the drying process. Prewetting CSs provides additional internal water that facilitates cement hydration during drying, promoting the formation of stratlingite (C2ASH8), a key hydration product that enhances mechanical properties after firing and promotes the early formation of anorthite. The firing at 800 °C and 1100 °C temperatures decreases compressive strength to a greater extent, as more CSs are in the composition. However, prewetting of CSs leads to significantly less deterioration (up to 32%, compared to compositions with non-prewetted CSs) in the compressive strength of refractory castables. The shrinkage of the refractory castable samples after firing at 1100 °C reached 0.16% in the case of non-prewetted CSs and 0.1% in the case of prewetted CSs. Prewetted CSs in refractory castables relaxes the stresses arising during firing more efficiently and practically compensates for shrinkage processes.